'It's the best way to learn' : Face-to-face attendance in university language courses. - Thomas, Bonnie; Caruso, Marinella; Tonkin, Kati; Brown, Josh; Kuuse, Sabine (Journal of University Teaching & Learning Practice v.22 n.1 p.1-29 https://doi.org/10.53761/ya57kz33, 2025)
The arrival of COVID-19 in 2020 marked a radical change to the university learning environment. With lockdowns and restrictions of various kinds, teaching and learning within the university had to shift to online and alternative modes of delivery within a short space of time. While life has gradually returned to 'normal' and students are increasingly physically present on campus, patterns of attendance and engagement seem to have altered. Although, anecdotally, many students have reported a renewed appreciation of face-to-face teaching - particularly in relation to learning a foreign language - there appears to be an overall drop in on-campus attendance since COVID. This study investigated students' reasons for attending or not attending face-to-face language classes. The aim was to inform changes to the teaching and delivery of our courses that could increase student attendance, engagement and overall retention. Through an online survey focusing on different factors that influence student attendance - using a combination of multiple choice, ranking, and open-ended questions - the study identified key reasons for students' decisions around class attendance. [Author abstract]